2015
DOI: 10.4028/www.scientific.net/amm.798.632
|View full text |Cite
|
Sign up to set email alerts
|

A Contact Nonlinear Thermo-Structure Fully-Coupled Simulation for Nozzle Based on One-Time Adhesive Failure

Abstract: To simulate a fully-coupled thermo-structure of a nozzle with adhesive failure, a flow field result is obtained based on a grid-independent check. The heat transfer coefficient along the nozzle is gained by Bartz formulation as an initial condition for thermo-structure simulation. A check for interface failure based on the adhesive, GD414, property is done to investigate the failure behavior, also to gain a simplified interface treatment. The gaps are chosen by experience. Then the simulation is carried out. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These boundaries mainly arise from the internal flow. Previous research has proved that the quasi-one-dimensional isentropic flow analysis can be used to predict the boundary conditions in the thermo-structural simulation for SRM nozzle [20,21]. Therefore, the both boundaries are calculated by quasione-dimensional isentropic flow field, as shown in Figure 3.…”
Section: Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…These boundaries mainly arise from the internal flow. Previous research has proved that the quasi-one-dimensional isentropic flow analysis can be used to predict the boundary conditions in the thermo-structural simulation for SRM nozzle [20,21]. Therefore, the both boundaries are calculated by quasione-dimensional isentropic flow field, as shown in Figure 3.…”
Section: Assumptionsmentioning
confidence: 99%
“…Therefore, the both boundaries are calculated by quasione-dimensional isentropic flow field, as shown in Figure 3. The relationship of temperature, pressure and Mach number at any section along the nozzle axis can be expressed as [20,21]:…”
Section: Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [32] simulated the fully-coupled thermo-structural response of a nozzle with adhesive failure, and the results showed that treating the interface as contact status could reduce the stress intensity. Goyal et al [33] simplified the traditional 3D method, and found that a 2D model could achieve acceptable results.…”
Section: Introductionmentioning
confidence: 99%